Group of three women with 1200 points wearing their Jackson AA blazers, June 13, 1935 - Munro, Melville S. (Tufts Archival Research Center, 2005)
8x10; (left to right) Esther Odell, Patricia Smith, and Ella Munro; Munro Scrapbook: Vol. 43, Box No. 62, Pg. 103.